Outcomes of upper gastrointestinal bleeding are similar between direct oral anticoagulants and vitamin K antagonists. Issue 6 (5th January 2021) - Gouriou, Claire; Bouguen, Guillaume; Lahmek, Pierre; Pelaquier, Agnes; Arotcarena, Ramuntxo; Garioud, Armand; De Montigny‐Lenhardt, Stephanie; Pauwels, Arnaud; Zanditenas, David; Charpignon, Claire; Combes, Remi; Nahon, Stephane; et al.
Summary: Background: The increased risk of upper gastrointestinal bleeding (UGIB) related to direct oral anticoagulants (DOACs) as compared to vitamin K antagonists (VKA) remains debated. Aims: To describe the epidemiology and outcomes of UGIB in patients treated with oral anticoagulants. Methods: A prospective, multicentre study in French general hospitals enrolled all consecutive patients with UGIB during one year. Patients treated with oral anticoagulants were retrieved from the cohort. Main outcomes were mortality and rebleeding during the first 6 weeks and need for non‐endoscopic treatment (surgery or interventional radiology). Results: Among the 2498 patients included, 475 (19%) had an oral anticoagulant, mostly with VKA (267 patients [56.2%]). Baseline characteristics were similar between the groups except for renal failure and cirrhosis that were more prevalent in the VKA group. Gastroscopy was normal in 73 patients (15.3%); peptic lesions were the main cause of UGIB (n = 233, 49%). Endoscopic treatment was performed in 128 patients (26.9%), leading to bleeding resolution in 74% (n = 95). Mortality rate at 6 weeks was 12.4% (59 patients), and was higher in the VKA group compared to DOACs (16.1% vs 7.8%, P < 0.01). By multivariate analysis, only the Charlson index ≥ 5 and UGIB occurrring in in‐patients were independently associated with mortality. Rebleeding (56 patients [11.8%]) and need for non‐endoscopic treatment (18 patients [3.8%]) were not associated with the type of anticoagulant. Conclusion: DOACs do not alter outcomes of UGIB as compared to VKA. Comorbidities and associated treatment are the most important factors worsening the prognosis of UGIB.